Pre-Service Teachers’ Assessment of Student Learning In Science Education - Coronado, Edsel O (Journal of Education in Black Sea Region, 2019)
This research was conducted to examine the tools, strategies, and problems encountered in assessing student learning by pre-service teachers in science during their on-and-off campus clinical experience. An explanatory sequential mixed method design was used in the study. Three instruments were used in this study: The Assessment Checklist for Student Teachers in Science, Focus Group Discussion (FGD) Questions, and the In-depth Interview Questions. 17 pre-service teachers participated from one teacher education institution. Findings of the study using Kruskal-Wallis One-way Analysis of Variance and Thematical Analysis using Phenomenological Reduction Method revealed the assessment tools used most frequently and least frequently, assessment strategies, and the problems encountered by pre-service teachers in science in assessing student learning. The findings also revealed that there was a significant difference in the use of rubric (p value=0.045) as the least frequently used assessment tool by pre-service teachers in science when grouped according to specialization.